Hubungan Antara Kecerdasan Emosional Dengan Stres Dalam Menyusun Skripsi Pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Lestari, Septina Dwi, Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2017)
Stress is a psychological condition characterized by physical symptoms, emotional, intellectual, and interpersonal skills when facing pressure in his thesis. One of the factors that influence the stress is emotional intelligence. This study aims to determine the relationship between emotional intelligence and stress in his thesis, the stress level in the thesis and the level of emotional intelligence and effective contribution of emotional intelligence and stress in his thesis. Researchers used the research subject as many as 80 students with accidental sampling technique. The results of the correlation coefficient (r) of -0.596 with sig. (One-tailed) = 0,000; p <0.01 indicates no significant negative relationship between emotional intelligence and stress in his thesis. Based on the results of analysis of emotional intelligence variables have the empirical mean (RE) amounted to 113.80 and the mean hypothetical (RH) of 95 which means emotional intelligence research subject is high. Variable stress in his thesis have empirical mean (RE) of 97.29 and the mean hypothetical (RH) of 107.5, which means stress in his thesis research subjects classified as moderate. Effective contribution of emotional intelligence by 35.5% to stress in his thesis.